Advancing radioactive material research method: the development of a novel in situ particle-attached microfluidic electrochemical cell - Yao, Jennifer; Tripathi, Shalini; McNamara, Bruce K.; Lahiri, Nabajit; Riechers, Shawn L.; Chatterjee, Sayandev; Reilly, Dallas D.; Ilton, Eugene S.; Buck, Edgar C. (Frontiers in Nuclear Engineering, 2023)
Introduction: This study aims to develop a microgram-scale microfluidic electrochemical cell (E-cell) for investigating the redox behavior of uranium oxide (UO2). The traditional bulk electrochemical methods may require shielded facilities to investigate the hazardous materials, e.g., spent nuclear fuel, due to high radiation levels. Microfluidic E-cells offer advantages such as reduced radiation exposure, control over fluid flow rates, and high-throughput capabilities. Methods: The design of the E-cell considers electrode morphology, adhesion to a thin membrane, electrode configuration, and vacuum compatibility. Three techniques, including FIB-SEM lift-out, Au coating, and polyvinylidene fluoride (PVDF) binder, are explored for fabricating and attaching microgram quantities of UO2 as working electrodes. The PVDF binder method proves to be the most effective, enabling the creation of a vacuum-compatible microfluidic E-cell. Results and discussion: The PVDF binder method demonstrates successful electrochemical responses and allows for real-time monitoring of UO2 electrode behavior at the microscale. It offers chemical imaging capabilities using in situ SEM/EDS analysis. The technique provides consistent redox outcomes similar to bulk electrochemical analysis. Conclusion: The development of a microgram-scale microfluidic electrochemical cell using the PVDF binder technique enables the investigation of UO2 redox behavior. It offers a low-risk approach with reduced radiation exposure and high-throughput capabilities. The technique provides real-time monitoring and chemical imaging capabilities, making it valuable for studying spent nuclear fuel systems and material characterization.